ANALISIS FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI POLA KONSUMSI PANGAN RUMAHTANGGA PETANI SAYURAN DI KOTA PEKANBARU - Novandri Ain; Djaimi Bakce; Novia Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Agricultural land, especially vegetable commodities in Pekanbaru City was decreases. Based on the situation, the prosperity and sustainability of vegetable farming in Pekanbaru City is questioned. The purpose of this research are analyze the structure of income, consumption patterns, and welfare level of vegetable farmers in Pekanbaru City. Analysis of income structure and multinomina logistic regression method was used to answer the problem of this research. Based on the results of the income structure analysis, the largest household income are comes from vegetable farming. The patterns of household consumption of vegetable farmers in Pekanbaru City shows that the allocation of food consumption expenditure are greater than non-food consumption. This indicated that the level of household welfare of vegetable farmers in Pekanbaru City are to be low.          The most dominant factors are affecting household consumption patterns of vegetable farmers are household income, number of family members, and education level. The greater of the household’s income are causes the smaller proportion of food consumption expenditure. However, the increasing number of household members are causes the allocation of food consumption expenditure is to be greater. In order to improve the household welfare of vegetable farmers, concrete policies are needed to increase the income of rumors and to reduce the birth rate in the household. This can be overcome by implementing government’s policies in subsidizing of production inputs and implementing family planning programs. In addition, efforts are needed to improve the knowledge of farmers through training and counseling. Keywords: Structure of Income, Consumption Patterns, Welfare